Facebook Social Games - Kinder-Kurlanda, K.; Willson, Michele (Walter de Gruyter GmbH & Co KG, 2016)
The popularity of Facebook social games is usually attributed to factors in the three areas of social interaction, play experience and the possibility for easy, casual play (Kinder-Kurlanda, 2012). It is, however, unclear, how these factors relate to the everyday lives of the largest user group, namely female players over the age of 35. An exploratory study of Australian players of Facebook social games was conducted to shed some light on gender-specific play behaviour in everyday circumstances (Willson, 2015a, 2015b). A similar study is planned for the German context.